2
$\begingroup$

I have one doubt about the following problem, maybe some of you can give me a hint to finish it.

Let $R$ be a commutative ring with identity and suppose the only ideals of $R$ are $(0),I,R$. Prove:

(a) If $x \notin I$ then $x$ is a unit.

(b) If $x,y \in I$ then $xy=0.$

Proof: (a) Suppose $x \notin I$ then $x+I \neq I$ and since $I$ is maximal we have $R/I$ a field, then there exist $y \in R-I$ such that $xy+I=1+I$, then $xy-1+I=I$ and then $xy-1 \in I$ and it implies $xy-1+1=xy$ is a unit, since $I$ is the only maximal (Here I am using the fact that $x$ is in the intersection of all maximal ideals of $R$ if and only if $1-xy$ is a unit for all $y\in R$). From $xy$ a unit we have the existence of $v$ such that $xyv=1$ then $x(yv)=1$ then $x$ is a unit.

(b) Suppose $x,y \in I$, then the ideals $(x),(y),(xy) \subset I$ but since the only ideals are $(0),I$ and $R$ we just have a few options for these ideals. If $(x),(y)$ or $(xy)$ are the trivial ideal $(0)$ then we are done. Suppose, then that $(x)=(y)=(xy)$, then we know that $x=uy$ for some unit $u$ of $R$, then we have $(x)=(x^2)$... I would like to conclude a contradiction from this, can I do this?

I am gonna be thankfull for any hint for this problem.

Thank you so much people!

$\endgroup$
  • $\begingroup$ In (a): I think you mean $xy + I = 1 + I$. How are you getting from $xy - 1\in I$ to $xy - 1 = 0$? $\endgroup$ – Stahl Dec 3 '16 at 23:16
  • $\begingroup$ I am sorry, it was a mistake. I am gonna edit the correct. It is wrong. $\endgroup$ – bttmbrcelo Dec 3 '16 at 23:17
  • $\begingroup$ Thank you, now I think the answer is complete, for (a). haha $\endgroup$ – bttmbrcelo Dec 3 '16 at 23:22
3
$\begingroup$

As to (a), just note that $(x)$ is an ideal containing $x \notin I$, therefore $(x) = R$, and thus there is $y \in R$ such that $x y = 1$.

As to (b), if $x y \ne 0$ then $(x y) = I$. But since $I \supseteq (x) \supseteq (x y)$, also $(x) = (x y) = I$, and thus there is $z \in R$ such that $x y z = x$, and $x (1 - y z) = 0$. But $1 - y z \notin I$ as $1 \notin I$ and $y z \in I$, so that $1 - y z$ is invertible, and $x = 0$, a contradiction.

$\endgroup$
  • $\begingroup$ Thank you! Is it a hint with another way to solve part (a), okay?? Do you know how can I see that xy=0 in part (b)? $\endgroup$ – bttmbrcelo Dec 3 '16 at 23:26
  • $\begingroup$ Yes. I have also added a solution for part (b), although there must be a simpler one. $\endgroup$ – Andreas Caranti Dec 3 '16 at 23:29
  • $\begingroup$ Thank you, it was perfect!!! I forgot trying to use part (a) again! $\endgroup$ – bttmbrcelo Dec 3 '16 at 23:36
  • $\begingroup$ You're welcome! $\endgroup$ – Andreas Caranti Dec 3 '16 at 23:36

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.